Implementasi Teknologi Interactive Projection Sebagai Media Tampilan Produk UMKM - Ashafidz Fauzan Dianta; Fony Revindasari; Zakha Maisat Eka Darmawan; Aris Sudaryanto; Kholid Fathoni (Sekawan Institut, 2025)
To increase the attractiveness of promotion for small & medium enterprises, the use of exhibition booths is an effective tool to promote a product or service. With a limited booth size, it can limit the number of products or information that can be displayed. The number of participants at an exhibition makes booth owners have to compete hard to attract visitors' attention. The use of immersive technology through interactive booths is an innovative solution that answers marketing challenges in today's digital era. This study develops an interactive booth using Interactive Projection technology to create a new experience for visitors. This interactive booth creates an environment that seems real and allows visitors to interact directly with the product. Creating product information content that is presented in an interesting and interactive way can attract visitors' attention. The Villamil-Molina method is used in development, where this method is one of the popular methods in multimedia software development. The stages of this method consist of: development, pre-production, production, post-production, and delivery. The results show that interactive booths can be used as a realistic and attractive small & medium enterprises product promotion media for visitors, and can increase engagement, and provide an immersive experience. This technology can be used as a promotional media, as well as supporting the introduction of modern technology to the wider community. Thus, interactive booths have the potential to be an efficient alternative solution for small & medium enterprises in strengthening their brands and expanding their market reach.